PENGARUH KEBIJAKAN DEVIDEN DAN KEBIJAKAN HUTANG TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2019-2023 - Riska Ramadani; Tartila Devy (CAPITALIS: JOURNAL OF SOCIAL SCIENCES, 2025)
This scholarly inquiry endeavors to delve into the intricate nexus between dividend policies and debt strategies in shaping the enterprise value of manufacturing firms enlisted on the national stock exchange over a specified temporal span. Adopting a positivist paradigm, the investigation relies on secondary data culled from publicly accessible financial disclosures hosted by the capital market authority’s official repository. Analytical scrutiny is executed via a multivariate linear regression framework, supplemented by inferential testing facilitated through advanced statistical computing software. The empirical findings unveil that the allocation of corporate earnings in the form of dividends exerts negligible influence upon the valuation of the firm. Such a revelation underscores the notion that the magnitude of dividend payouts does not substantially sway investor judgment regarding a company’s intrinsic worth. In stark contrast, leverage policies reflected in the utilization of borrowed capital manifest a statistically salient impact, implying that heightened debt levels, when judiciously employed, can act as catalysts for amplifying firm value. When both financial strategies are appraised in tandem, a collective albeit modest effect is discerned, indicating a nuanced interplay between the two in determining firm valuation. This scenario intimates that dividend and debt decisions alone are insufficient to encapsulate the multifaceted nature of firm value determinants. Accordingly, subsequent inquiries are urged to incorporate a broader spectrum of explanatory variables to foster a more holistic comprehension of the underlying dynamics that govern corporate worth in the contemporary financial landscape.